Characterization and Simulation of the Effect of Punching on the High Cycle Fatigue Strength of Thin Electric Steel Sheets. (2015) - Dehmani, Helmi; Brugger, Charles; Palin-Luc, Thierry; Mareau, Charles; Koechlin, Samuel
Abstract: Rotors of electric machines are built from stacks of thin steel sheets. The fabrication process of these components usually involves punching operations that generate defects on the steel sheet edges. In this study, high cycle fatigue tests are performed on punched and polished edges specimens to investigate the effect of the punching process on the fatigue behaviour of these thin sheets. Results show a significant decrease of the fatigue strength for punched specimens. SEM observations of fracture surfaces reveal that crack initiation always occurs on a punching defect. Residual stresses on punched edges are analysed using X-Ray diffraction techniques. High tensile residual stresses along the loading direction are found. Some specimens edges were scanned using 3D topography prior to the fatigue tests. This allows for identifying the real geometry of the most critical defect. Murakami criterion was then evaluated in order to take into account the effect of defects. The best trend of the experimental results is given when residual stresses are taken into account. Local elastic stresses for 3 defects geometries have been calculated using FEA. Crossland fatigue criterion has been evaluated to try accounting for the local stress state around defects. Results show that the assessed fatigue strength is overestimated using this criterion.